Induction of opsonophagocytic killing activity with pneumococcal conjugate vaccine in human immunodeficiency virus-infected Ugandan adults - Chena, Meng; Ssali, Francis; Mulungi, Maureen; Awio, Peter; Furumoto, Akitsugu; Kityo, Cissy; Mugyenyi, Peter; Oishi, Kazunori (Vaccine, 2008)
The levels of IgG determined by ELISA may have limited relevance in human immunodeficiency virus (HIV)-infected adults because of non-functional antibodies. 58 HIV-1-infected and 29 HIV-uninfected Ugandan adults were immunized with conjugate vaccine (CV) followed by polysaccharide vaccine (PV) after a 2-month interval, and the opsonophagocytic killing (OPK) titers against serotype 4 or 14 pneumococcal strains as well as the levels of serotype-specific IgG in sera were determined. Significant increases were found in the OPK titers and IgG levels for both serotypes after CV vaccination irrespective of HIV status. Increases in IgG levels and OPK titers were largely dependent on the CD4+ cell counts, except for increases in the IgG levels for serotype 4. The proportions with serum OPK titer equal to or greater than 8 were 0–4.3% for serotype 4 and 26.7–42.9% for serotype 14 before vaccination, but the proportions increased up to 43.3–86.2% for serotype 4 and 63.3–96.6% for serotype 14 in all three groups 2 months after CV vaccination. The serum OPK titers remained at levels higher than the pre-vaccination level for at least 8 months after CV vaccination. A single dose of CV could afford some protective immunity in HIV-infected African adults before the introduction of antiretroviral therapy.
Keywords: Pneumococcal conjugate vaccine; Pneumococcal polysaccharide vaccine; Serotype-specific IgG; Opsonophagocytic killing; HIV-infected adults